P476 Effectiveness and safety of ustekinumab in ulcerative colitis: Real-world evidence from the ENEIDA registry. (27th May 2021) - Chaparro, M; Garre, A; Iborra, M; Sierra, M; Barreiro-de Acosta, M; Fernández-Clotet, A; de Castro, L; Boscá-Watts, M; Casanova, M J; López-García, A; Lorente, R; Rodríguez, C; et al.
Abstract: Background: The development program (UNIFI) has shown promising results of ustekinumab in ulcerative colitis (UC) treatment that should be confirmed in clinical practice. Aims: Primary: to evaluate the durability of ustekinumab treatment in UC patients in clinical practice. Secondary: to assess the short-term response (at week 16) and the long-term effectiveness (at maximum follow-up) and to assess the safety of ustekinumab in clinical practice. Methods: Patients included in the prospectively maintained ENEIDA registry who received at least one intravenous dose of ustekinumab due to active UC [Partial Mayo Score (PMS) >2] were included. Clinical activity and effectiveness were defined based on PMS. Results: 95 patients were included (table 1). At week 16, 53% of patients had clinical response (including 35% of patients in remission) (figure 1). In the multivariate analysis, elevated serum C-reactive protein was the only variable significantly associated with clinical remission. Long-term remission is represented in figure 2. 36% of patients discontinued the treatment with ustekinumab during a median follow-up of 31 weeks. The probability of maintaining ustekinumab treatment was 87% at week 16, 63% at week 56, and 59% at week 72 (figure 3); primary failure was the main reason for ustekinumab discontinuation. No variable was associated with risk of discontinuation. Three patients reported adverse events; one of them had a fatal severe SARS-CoV-2 infection. Conclusion: Ustekinumab is effective both in the short and the long-term in real-life, even in a highly refractory cohort. Higher inflammatory burden at baseline correlated with lower probability of achieving remission. Safety was consistent with the known profile of ustekinumab.